Evaluación del impacto de la inversión en investigación y desarrollo y el número de investigadores en el crecimiento económico; Assessment of the impact of investment in research and development and the number of researchers on economic growth - Alí Aali-Bujari; Francisco Venegas-Martínez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– This research analyzes the impact of investment in Research and Development (R&D) and the number of researchers on the economic growth of some of the economies of the Organization for Economic Cooperation and Development (OECD), for the period 1996-2016. A causality analysis in the sense of Granger is performed and a panel data model is estimated. Data are obtained from the World Bank. There is empirical evidence of bidirectional causality between R&D and GDP per capita, but predominantly R&D Granger-causes GDP. Bidirectional causality is also found between the number of researchers and GDP per capita, but predominantly GDP Granger-causes the number of researchers. While the dynamic panel model of the MGM system in one stage shows that economic growth is positively affected by investment in R&D and the number of researchers. This work differs from others in the following aspects: 1) it considers a sample of 25 OECD countries in the period 1996-2016; 2) there is a greater availability of data, and 3) a dynamic panel data analysis is carried out that allows the use of a greater number of countries, variables and periods.
Keywords: O10; O30; O40; 330; investment in research and development; number of researchers; economicgrowth; Granger causality; panel data